Working Knowledge: Catalogers and the Stories They Tell - Belantara, Amanda; Drabinski, Emily (KULA, 2022)
Cataloging librarians make myriad choices every day as they create the metadata necessary for information retrieval.  Each record represents an interaction between the cataloger and the systems they work within and, sometimes, against. Their work is highly constrained by standardized machine-readable fields and codes, controlled subject terms and classification schema. In the exploratory research project Catalogers at Work, the authors use sound recording to reveal the complex yet hidden negotiations embedded in library catalog records.